Potentiometric Response of Ag/AgCl Chloride Sensors in Model Alkaline Medium. (28th June 2018) - Pargar, Farhad; Kolev, Hristo; Koleva, Dessi A.; van Breugel, Klaas
Abstract : The stability and reproducibility of an Ag/AgCl sensors' response in an alkaline medium are important for the application of these sensors in cementitious materials. The sensors' response, or their open circuit potential (OCP), reflects a dynamic equilibrium at the sensor/environment interface. The OCP response in an alkaline medium is affected by the presence of hydroxide ions. The interference of hydroxide ions leads to inaccuracies or a delay in the sensors' response to a certain chloride content. In this article, the potentiometric response (or OCP evolution) of the chloride sensors is measured in model solutions, resembling the concrete pore water. The scatter of the sensors' OCP is discussed with respect to the interference of hydroxide ions at varying chloride concentration in the medium. The deviation of the sensor's response from its ideal performance (determined by the Nernst law) is attributed to dechlorination of the AgCl layer and the formation of Ag2 O on the sensor's surface. Results from the surface XPS analysis of the AgCl layer before and after treatment in alkaline medium confirm these observations in view of chemical transformation of AgCl to Ag2 O.